Exploring neoantigens and genetic profiles in renal cell carcinoma: a study of Iranian patients - Zohreh Mehmandoostli; Mahmood Dehghani Ashkezari; Seyed Morteza Seifati; Amirreza Farzin; Gholam Ali Kardar (Journal of Current Oncology and Medical Sciences)
Introduction: Kidney cancer accounts for 3.7% of all newly diagnosed cancer cases and represents a considerable global health challenge. Although there have been advancements in treatment, renal cell carcinoma (RCC) continues to show resistance to conventional cytotoxic chemotherapy, highlighting the need for innovative therapeutic strategies. Current research is focusing on vaccine approaches that target tumor neoantigens, utilizing next-generation sequencing to pinpoint tumor-specific mutations. A deeper understanding of the molecular characteristics of RCC, particularly gene mutations such as BAP1, PBRM1, SETD2, and VHL, is essential for the development of personalized treatment modalities. This study aimed to investigate potential tumor neoantigens in samples from Iranian patients diagnosed with RCC, with an emphasis on peptide sequences that exhibit a strong binding affinity for Iranian Human Leukocyte Antigen (HLA).